2006
DOI: 10.1111/j.1365-3180.2006.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to flooding intensity in Elytrigia repens, E. intermedia (Poaceae: Triticeae) and their hybrid

Abstract: Summary Response to flooding intensity in three closely related taxa, Elytrigia repens, E. intermedia and their hybrid was studied. Plants were exposed to three intensities of flooding for a 30‐day period. Response to flooding intensity was estimated by measuring dry mass of the following: total biomass, above‐ground living biomass, above‐ground dead biomass, below‐ground biomass, rhizome and root mass and by the allocation of dry mass into rhizomes and root:shoot ratio. Reduction of nearly all the biomass com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…However, waterlogging decreased the growth of these two species much less than that of flood-sensitive species [34][36], and even the 60 cm waterlogging treatment did not result in the death of any of the plants. Therefore, both species have a high capacity to tolerate waterlogging.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, waterlogging decreased the growth of these two species much less than that of flood-sensitive species [34][36], and even the 60 cm waterlogging treatment did not result in the death of any of the plants. Therefore, both species have a high capacity to tolerate waterlogging.…”
Section: Discussionmentioning
confidence: 86%
“…However, in the present study, the growth traits of A. philoxeroides were decreased less than those of A. sessilis under waterlogging conditions, indicating lower plasticity of growth traits (Table 1, Figures 1, 2 and 4). Previous studies generally showed that the negative impacts are greater in flood-sensitive plants than in flood-tolerant plants [23], [34], [38]. The flood-tolerant plants are often characterized by restricted growth performance and conservation of energy and carbohydrates, especially during complete flooding [24].…”
Section: Discussionmentioning
confidence: 99%
“…Genotype integrity of this species is maintained in optimal habitats, while introgressed individuals are favoured in marginal habitats (Choler et al 2004). Studies on flooding tolerance of Elytrigia repens, E. intermedia and their hybrids have shown that hybridization may lead to the enrichment of hybrids gene pools with genes responsible for the survival of the parental species under extreme conditions (Mahelka 2006). CONCLUSIONS AFLP analyses and the level of pollen fertility unambiguously support the hybrid origin of Elymus ×mucronatus.…”
Section: Genetic Evidence For Hybridization Between Elymus Repens Andmentioning
confidence: 84%
“…It appears that E. hispidus occurs primarily in the habitats studied, on the loess in Smoniowice and calcareous soils in Kielce. E. hispidus is adapted to a narrow range of environmental conditions and displays rather low phenotypic plasticity (Szczepaniak 2001;Mahelka 2006). The disturbance of agricultural activities in habitats on the field margins (in Smoniowice) and in the quarry neighbouring on a meadow (in Kielce) caused the disappearance of the more susceptible parental species E. hispidus and the spread of the better adapted hybrid specimens.…”
Section: Genetic Evidence For Hybridization Between Elymus Repens Andmentioning
confidence: 99%
“…Flooding tolerance of E. repens is expected, since it is a highly-adaptive species growing in a wide variety of habitats, including alluvial flooded meadows and periodically flooded habitats [156,157] together with the fact that plants with sufficient rhizome mass are able to survive oxygen deficiency ( [158] reported that E. repens survived a 50-day flood). However, longer flooding periods and long duration of anoxia in particular may be harmful to E. repens.…”
Section: Soil Disinfestationmentioning
confidence: 99%